Evaluating Surgeon Estimation of Cup Position in Total Hip Arthroplasty: A Cadaver Study - Vigdorchik, Jonathan M.; Cross, MIchael B.; Miller, Theodore T.; Bogner, Eric A.; Muir, Jeffrey M.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2017)
Inaccurate placement of components during total hip arthroplasty (THA) can lead to significant postoperative complications including revision surgery. Traditionally, surgeons grossly estimate component positioning intraoperatively using anatomical landmarks; however, evidence indicates that this surgeon assessment may not be reliable. The purpose of this study was to determine the accuracy of surgeon estimates of component position as compared with imaging (radiographs and computed tomography [CT] scan) and a new surgical navigation system. Three board-certified orthopaedic surgeons each performed four THA procedures on six cadavers (12 hips). Radiographs and CT scans were obtained postoperatively. The “gold standard” measurements of implanted cup anteversion and inclination were derived from three-dimensional renderings created from postoperative CTs. A reference value for cup position was created by aligning the anterior pelvic plane in each rendering coplanar with the CT table. Following each procedure, surgeons provided their estimate of acetabular cup component orientation. Surgeon estimates were compared with data gathered from postoperative radiographs, CT scans, and the navigation device. Surgeon estimates of anteversion and inclination were within 10 degrees of reference values in 64% (7/11) and 82% (9/11) of cases, respectively. Surgeon estimates of anteversion differed from reference values by a mean of 7.6 ± 5 degrees, whereas inclination differed from reference values by a mean of 6.1 ± 5.1 degrees (all means absolute). Radiographic measurements differed from reference values by 7.8 ± 4.3 degrees (p > 0.05) and 2.7 ± 2.3 degrees (p = 0.06) for anteversion and inclination, respectively, whereas CT values differed by 2.5 ± 1.6 degrees (p = 0.004) and 2.3 ± 2.1 degrees (p = 0.04). The navigation system differed from reference values by 4 ± 4 degrees (p = 0.08) and 4.2 ± 3.2 degrees (p = 0.31). Surgeons underestimated anteversion and inclination by 7.7 ± 4.8 degrees and 6.9 ± 4.8 degrees, respectively. Surgeon underestimation was observed in 8/11 (73%) cases, with anteversion underestimated by > 5 degrees in 5/8 (62%) cases and inclination underestimated by > 5 degrees in 4/8 (50%) cases. Our findings suggest that surgeons tend to underestimate both anteversion and inclination and that the accuracy of their estimates is similar to that of radiographs. CT scans and the navigation system were able to provide more accurate measurements of cup position.
Keywords: total hip arthroplasty; cup position; surgeon estimate; imaging; navigation